2011
DOI: 10.4161/epi.6.2.13627
|View full text |Cite
|
Sign up to set email alerts
|

EAR motif-mediated transcriptional repression in plants

Abstract: Ethylene-responsive element binding factor-associated Amphiphilic Repression (EAR) motif-mediated transcriptional repression is emerging as one of the principal mechanisms of plant gene regulation. The EAR motif, defined by the consensus sequence patterns of either LxLxL or DLNxxP, is the most predominant form of transcriptional repression motif so far identified in plants. Additionally, this active repression motif is highly conserved in transcriptional regulators known to function as negative regulators in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
186
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(188 citation statements)
references
References 50 publications
(82 reference statements)
2
186
0
Order By: Relevance
“…To discriminate between the situation where the absence of activity is due to the lack of binding to the target promoter from those where the ERF binds but remains neutral on the promoter activity, we used chimerical constructs as effectors consisting of ERF coding sequences fused to the SRDX repressor motif [45]. Since the dominant repression activity of the chimerical construct is mediated by epigenetics mechanisms [46], the absence of repression with any of the ERF-SRDX constructs can be interpreted as resulting from the incapacity of the ERF to recognise the target promoter. Figure 3A shows that ERF proteins can not only act as activators or repressors, but can also be neutral on the ethylene-responsive promoters.…”
Section: Resultsmentioning
confidence: 99%
“…To discriminate between the situation where the absence of activity is due to the lack of binding to the target promoter from those where the ERF binds but remains neutral on the promoter activity, we used chimerical constructs as effectors consisting of ERF coding sequences fused to the SRDX repressor motif [45]. Since the dominant repression activity of the chimerical construct is mediated by epigenetics mechanisms [46], the absence of repression with any of the ERF-SRDX constructs can be interpreted as resulting from the incapacity of the ERF to recognise the target promoter. Figure 3A shows that ERF proteins can not only act as activators or repressors, but can also be neutral on the ethylene-responsive promoters.…”
Section: Resultsmentioning
confidence: 99%
“…These family members possess a C terminal motif L/FDLNL/FxP designated as the ERF-associated Amphiphilic Repression (EAR) motif that has been shown to be involved in repression not only in association with the AP2 domain but also in other transcription factors, such as C2H2 zinc finger proteins and AUX/IAA proteins, that lack the AP2 domain (Kagale et al , 2010; Kagale and Rozwadowski, 2011). In combination with the AP2 domain, there are eight members each of the EAR motif containing genes in Arabidopsis and rice (Nakano et al , 2006) and at least seven in tomato (Sharma et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report has suggested that transcription factors carrying this EAR motif form a complex with co-repressors and histone deacetylases (HDAs), favoring a closed chromatin structure to repress transcription [56]. Motif 15, containing the SP(T/V)SVL sequence, is found in group VI.…”
Section: Discussionmentioning
confidence: 99%